Association between nailfold capillaroscopy abnormalities and autoimmune disease in pediatric populations. Issue 2 (25th January 2022) - Li, Andraia R.; Burke, Connor D.; Purvis, Colby S.; Lee, Lara Wine
Abstract: Objective: Time to diagnosis of autoimmune disease in pediatric populations can take years but nailfold capillaroscopy (NFC) may identify early signs of autoimmune disease. The aim of this study is to assess the association between nailfold capillary abnormalities and autoimmune disease in children. Methods: A systematic search of PubMed, EMBASE, and Scopus was performed to identify all studies published before March 17, 2021. Observational studies reporting NFC outcomes in children with autoimmune disease and healthy controls (HC) were eligible for inclusion. Odds ratios (OR) and 95% confidence intervals (CI) were pooled using a random‐effects meta‐analytical model. Results: Nine of 3665 studies reporting on 641 patients (398 subjects, 243 controls) were included. Pediatric patients with autoimmune disease were 9.88 (95% CI 3.16–30.87, I 2  = 80.1%) times more likely to have abnormal nailfold capillaries than HC. Of the capillaroscopic features, dilated capillaries (OR 27.90, 95% CI 2.17–349.05, I 2  = 59.9%) were the most likely abnormality observed on NFC. This was followed by the likelihood of reduced capillary density (<7 capillaries/mm) (OR 19.91, 95% CI 3.79–105.52, I 2  = 0%), giant capillaries (OR 12.87, 95% CI 2.38–69.45, I 2  = 0%), hemorrhages (OR 13.89, 95% CI 5.34–36.16, I 2  = 0%), and avascularity (OR 10.38, 95% CI 2.20–49.04, I 2  = 0%). Conclusions: Children with autoimmune disease are significantly more likely to have nailfold capillary abnormalities. NFC may be useful in identifying early signs of underlying rheumatic disease and potentially decrease the time to diagnosis for this patient population.